Al-Kafa`āh at-Ta’līmiyyah wa al-Mihniyyah ladā Mudarrisī al-Lughah al-‘Arabiyyah bi al-Madāris al-Mutawassiṭah al-Islamiyyah bi Manṭiqah Rembang Jāwā al-Wusṭā - Zainal Arifin (IAIN Salatiga, 2021)
This study aimed at describing the implementation of the pedagogic and professional competences of Arabic language teachers at Islamic Junior High Schools in Rembang Regency. This study used a descriptive qualitative method, with the populations were Arabic teachers at Islamic Junior High Schools in Rembang Regency. Samples were taken using proportional random sampling technique. The research data were collected using closed questionnaires, passive participation observation and semi-structured interview, and were processed with a frequency distribution table. The results indicate that Arabic teachers' pedagogical and professional competencies are fairly good with an average score of 3.97 and 3.57 on the Likert scale. However, the implementation of these two competencies among Arabic language teachers in learning activities is different and relatively low with an average score of 41.86%.